The Correlation between Small Placental Volume Measured by Three-dimensional Ultrasonography and Adverse Pregnancy Outcomes: An Observational Study - Papada Tubtimkhiao; Nawabhorn Orungrote; Supisara Mungkorntongsakul; Kornkarn Bhamarapravatana; Komsun Suwannarurk (Siriraj Medical Journal, 2024)
Objective: The placenta is a vital organ in the growth and development of fetuses within the uterus. The size of the placenta is positively associated with fetal well-being. The aim of this study was to investigate any potential correlation between placental volume and negative pregnancy outcomes.